{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

Assignment 3 Solutions

Assignment 3 Solutions - MATH 135 Fall 2010 Solution of...

This preview shows pages 1–2. Sign up to view the full content.

MATH 135, Fall 2010 Solution of Assignment #3 Problem 1 . Prove that n i =1 (2 i - 1) 2 = n (2 n - 1)(2 n +1) 3 for all n 1. Solution. When n = 1 we have n i =1 (2 i - 1) 2 = 1 2 = 1 and n (2 n - 1)(2 n +1) 3 = 1 · 1 · 3 3 = 1, so the claim is true when n = 1. Let k 1 and suppose the claim is true when n = k , that is suppose that k i =1 (2 i - 1) 2 = k (2 k - 1)(2 k +1) 3 . Then when n = k + 1 we have = k +1 X i =1 (2 i - 1) 2 = k X i =1 (2 i - 1) 2 + (2 k + 1) 2 = k (2 k - 1)(2 k + 1) 3 + (2 k + 1) 2 = (2 k + 1) k (2 k - 1) 3 + (2 k + 1) = (2 k + 1) k (2 k - 1) + 3(2 k + 1) 3 = (2 k + 1)(2 k 2 - k + 6 k + 3) 3 = (2 k + 1)(2 k 2 + 5 k + 3) 3 = (2 k + 1)( k + 1)(2 k + 3) 3 Thus the claim is true when n = k + 1. By Mathematical Induction, the claim is true for all n 0. Problem 2 . Let a 0 = 1 and a 1 = 1 and for n 2 let a n = 2 a n - 1 + 2 a n - 2 . Show that we have a n = 1 2 ( (1 + 3) n + (1 - 3) n ) for all n 0. Solution. When n = 0 we have a n = a 0 = 1 and 1 2 ( (1 + 3) n + (1 - 3) n ) = 1 2 ( (1 + 3) 0 + (1 - 3) 0 ) = 1 2 ( 1 - 1 ) = 0, so the claim is true when n = 0. When n = 1 we have a n = a 1 = 1 and 1 2 ( (1+ 3) n +(1 - 3) n ) = 1 2 ( (1+ 2) 1 +(1 - 3) 1 ) = 1 2 ( 1+ 3+1 - 3 ) = 1, so the claim is true

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}